부산시 외곽지역의 농촌을 배려한 활성화 방안 고찰 - 국내외 사례 분석을 중심으로 - 조충현(Choong Hyun Cho); 성이용(Lee-Yong Sung) (KIEAE Journal, 2024)
Purpose: The main target of social agriculture (care farm) for the agricultural population in areas such as Gangseo-gu, and Gijang-gun, which are outside Busan, is limited to the senior generation and the developmentally disabled, but the main target of the care farm in this study is to expand the research to children, families, and public/private organizations to propose a practical and effective social agricultural model in Busan. Method: First, social agriculture (care farm) is defined through a review of the literature and various data on problems in the Busan area and the selection of the Busan area are analyzed. Second, we derive domestic and foreign cases and the current status of the research target site. Third, we conduct research on care systems and agricultural production programs through domestic and international cases. Fourth, social agriculture suitable for the Busan area is proposed by deriving facility content proposals through domestic and international cases. Result: The structure of social agriculture (care farm) was transformed from the concept of care, education, jobs, and rehabilitation to a concept that includes experiences and experiences through a model that applied care systems and agricultural production programs, and agriculture, space, and programs were proposed by expanding not only the registered disabled and the super-aged population, but also the main users to children, families, and private/public organizations, which are socially disadvantaged. KCI Citation Count: 0